Spatial analysis of signal during epileptic seizure on plat electroencephalography - 608332 Goh, Chien Yong, 1987- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Ph.D (Matematik)) - Universiti Teknologi Malaysia, 2017